1997
DOI: 10.1007/bf02676545
|View full text |Cite
|
Sign up to set email alerts
|

Mesiodentes: Inzidenz, morphologie, ätiologie

Abstract: There are many publications in the literature focusing on clinical, radiological and surgical aspects of the treatment of mesiodentes. However, the etiology of this dental anomaly remains widely unclear. The purpose of this study was to evaluate etiologic factors for mesiodentes in a collective comprising 30 patients with a total of 45 mesiodentes. Thirty-one percent of the patients showed a familial disposition, pointing to inheritance as a key factor in the development of mesiodentes. Our results further sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 12 publications
1
47
0
8
Order By: Relevance
“…Although no investigation proved the hereditary condition of the mesiodens, it is quite possible, in view of the patients showing a familial disposition. 3 Many authors suggested inheritance as a key factor in the development of mesiodens. 2,3,7,10 Brook 11 postulated a multifactorial polygenic model of quasi-continuous traits for simultaneous consideration of supernumeraries, megadontia, oligodontia and microdontia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no investigation proved the hereditary condition of the mesiodens, it is quite possible, in view of the patients showing a familial disposition. 3 Many authors suggested inheritance as a key factor in the development of mesiodens. 2,3,7,10 Brook 11 postulated a multifactorial polygenic model of quasi-continuous traits for simultaneous consideration of supernumeraries, megadontia, oligodontia and microdontia.…”
Section: Discussionmentioning
confidence: 99%
“…2 Mesiodens appears to be more common in males than in females with a male-female ratio of 2:1. 3 Familial occurrence of mesiodens is reported to involve more than one sibling, or one generation. 2,[4][5][6] In some cases, this anomaly has also been seen in more than one generation.…”
mentioning
confidence: 99%
“…Genellikle süt ve daimi dentisyonun her ikisi de etkilenmektedir ancak daimi dentisyonda bu anomaliler daha yüksek oranda ortaya ç›kar. Yar›¤›n fliddeti, difller ve oklüzyonun gelifliminin yönünü ve boyutunu da belirler (1,2,(6)(7)(8)(9)(10)(11).…”
Section: G ‹ R ‹ Fiunclassified
“…Supernumerary teeth are most common in permanent dentition than the primary dentition and are most frequently found in maxilla than the mandible. Although several theories have been suggested about the cause of supernumerary teeth, the majority of supernumerary teeth are considered to develop as a result of horizontal proliferation or a hyperactivity of the permanent or deciduous dental lamina [1,7]. Moreover, heredity is believed to be an important etiological factor in the occurrence of supernumerary teeth.…”
mentioning
confidence: 99%
“…Many published cases of supernumerary teeth mentioned recurrence within the same family [5,6]. Also, many authors suggested inheritance as a key factor in the development of supernumerary teeth [6,7]. Multiple supernumerary teeth are usually associated with syndromes like cleidocranial dysplasia and Gardener syndrome and conditions such as cleft lip, palate or both.…”
mentioning
confidence: 99%